Nanocrystal magnetic material and preparation method thereof

By synthesizing Nb3VSe6 single crystal under high-temperature vacuum reaction conditions, the problem of lack of efficient and stable synthesis methods in the prior art is solved, the high-frequency response and unique resistance and temperature characteristics of the material are realized, and its application potential in many fields is expanded .

CN119419023AActive Publication Date: 2025-02-11UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202510019208.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The prior art lacks systematic in-depth research and efficient and stable synthetic methods to prepare Nb3VSe6 compounds with unique resistance temperature characteristics and magnetic properties, limiting their application in multiple fields.

Method used

High-quality Nb3VSe6 single crystals were synthesized by mixing the raw materials with a purity of more than 99.9% in a specific proportion, and using tellurium tetrachloride as a transporting agent under high-temperature vacuum reaction conditions, and using chemical vapor phase transport method.

Benefits of technology

It realizes the high-frequency response, low hysteresis loss and unique resistance temperature characteristics of Nb3VSe6 single crystal, expanding its application potential in high-frequency devices, spintronic components and magnetic dampers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419023A_ABST
    Figure CN119419023A_ABST
Patent Text Reader

Abstract

The invention discloses a nanocrystal magnetic material and a preparation method thereof, the nanocrystal magnetic material is a magnetic Nb3VSe6 crystal and comprises three elements, namely Nb, V and Se, the metered molar ratio of the three elements is 3: 1: 6, the crystal has a centrosymmetric broken hexagonal layered structure, the space group of the crystal is P6322, V atoms are inserted between two 2H-NbS2 hexagonal layers, the lattice constants a = b = 5.738, and c = 12.018. The magnetism in the material is mainly contributed by positive trivalent Cr ions, the magnetic moment is 3B, the local electron spin S is equal to 3 / 2, and conduction electrons are from unfilled bands of Nb atoms. Due to the unique crystal structure and electronic property, the material shows potential application value in multiple fields, especially in the aspects of high-frequency devices, spintronics elements, magnetic dampers and the like. The Nb3VSe6 single crystal is relatively stable in air, which is a great advantage for practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of novel material science and technology, and in particular to a nanocrystalline magnetic material and a preparation method thereof. Background Art

[0002] With the development of science and technology, the demand for new functional materials is increasing. Among many new materials, compounds with special physical properties have attracted wide attention due to their potential applications in sensors, electronic devices, magnetic equipment and other fields. In particular, materials that show the characteristic of resistance changing with temperature within a specific temperature range are one of the research hotspots. In addition, materials with both magnetic properties have attracted much attention due to their application prospects in data storage, magnetic resonance imaging (MRI) and other fields.

[0003] Nb 3 VsS 6 It is a new compound, and its unique resistance-temperature characteristics and magnetism make it show potential application value in many fields. However, the research on this compound is still in its early stages, and there is a lack of systematic and in-depth research reports. Therefore, developing an efficient and stable method to synthesize this compound and conducting detailed research on its physical and chemical properties is of great significance to promote scientific and technological progress in related fields.

[0004] In the field of low-dimensional magnetic materials, especially those that can exhibit ferromagnetic order in two dimensions or lower, such as Cr 2 Ge 2 Te 6 , Fe 3 Get 2 and Cr 3 VS 6 Their discovery and development have not only greatly expanded our understanding of the magnetic nature of materials, but also brought revolutionary changes to the field of spin electronics. The properties of these materials enable scientists to precisely manipulate the spin state of electrons at the nano and even atomic levels, which is crucial for the development of new spin electronic devices. The potential applications of these devices include but are not limited to future computer chips, data storage systems, sensors, and quantum computing, which are expected to bring higher efficiency, lower energy consumption, and smaller size.

[0005] It is worth noting that among these low-dimensional magnetic materials, the resistance behavior of specific materials shows unique properties as the temperature changes. For example, there is a material whose resistance increases with increasing temperature in the temperature range of 2-25K; and in the temperature range of 25-300K, this trend continues, that is, the resistance still increases with increasing temperature. 25K is considered to be a transition temperature point of this material, near which the resistance behavior of the material changes significantly. This special resistance-temperature relationship may be related to the magnetic transition inside the material, which is of great significance for a deep understanding of the magnetic and electrical transport properties of the material. This type of research not only helps us better understand the basic physical mechanisms of low-dimensional magnetic materials, but also provides important guidance for the design and optimization of high-performance spintronic devices. Summary of the invention

[0006] The object of the present invention is to provide a nanocrystalline magnetic material and a preparation method thereof.

[0007] In order to solve the above technical problems, the present invention is achieved through the following technical solutions: A Nb 3 VsS 6 Low-dimensional magnetic material and its resistance characteristic material at low temperature, the material is magnetic Nb 3 VsS 6 The crystal contains three elements, namely Nb, V and Se, and the molar ratio of the three elements is 3:1:6. Specifically, the atomic percentage of Nb is 30.83404%, the atomic percentage of V is 9.84943%, and the atomic percentage of Se is 59.31653%.

[0008] The crystal has a hexagonal layered structure with broken centrosymmetry and its space group is P6 3 22, V atoms are inserted between two 2H-NbS 2 Between the hexagonal layers, the lattice constants are a=b=5.738Å and c=12.018Å. The magnetism in the material is mainly contributed by the positive trivalent Cr ions, with a magnetic moment of 3µB and a localized electron spin of S=3 / 2, while the conduction electrons originate from the unfilled bands of Nb atoms. 3 VsS 6 The single crystal has a high frequency response: due to the strong exchange interaction between the magnetic moments inside the material, it can support very high-frequency magnetic oscillations, much faster than ferromagnetic materials. This is particularly valuable for high-speed data processing and communication technologies.

[0009] Nb 3 VsS 6 Single crystal is a material that exhibits unique resistance-temperature characteristics in the range from low temperature to room temperature. Specifically, in the temperature range of 2-25K, as the temperature increases, Nb 3VsS 6 The resistance of Nb increases gradually; this trend continues in the temperature range of 25-300K, which means that the resistance increases with the increase of temperature in the entire temperature range. 25K is considered to be the 3 VsS 6 A key transition temperature point is found in the material, near which the resistance behavior of the material changes significantly, which may be related to the transition of its internal magnetic state.

[0010] In addition to its unique resistance-temperature characteristics, Nb 3 VsS 6 Single crystals exhibit low hysteresis losses during magnetic field reversal. This means that when changing the magnetization direction, it does not need to overcome a large coercive force. This property makes Nb 3 VsS 6 It is particularly suitable for applications that require frequent switching of magnetic states, such as certain types of sensors or read / write heads. 3 VsS 6 The unique properties of single crystal materials make them an ideal platform for studying spintronic phenomena, especially the spin Hall effect at their interfaces, which can effectively manipulate the magnetic moments in antiferromagnetic materials, which is crucial for the development of a new generation of spintronic devices. Although antiferromagnetic materials are not traditionally used for information storage because their magnetization states are not easily detected and modified by external magnetic fields, recent studies have shown that efficient data storage solutions can be achieved by precisely controlling the movement of magnetic domain walls in antiferromagnetic materials or by utilizing antiferromagnetic resonance. Therefore, Nb 3 VsS 6 Single crystals have not only attracted attention for their low hysteresis loss and unique resistance-temperature characteristics, but also have shown great potential in the field of information storage, opening up new paths for the development of future spintronics and data storage technologies. Single crystal materials synthesized by chemical vapor transport require a sealed high-temperature furnace and precise temperature control, so the equipment is relatively complex and costly. And it often takes a long time, which affects production efficiency. And the success of single crystals depends largely on the fine control of growth conditions, including temperature gradients, types and amounts of transport agents, etc., which requires high experience and technical skills of experimental personnel.

[0011] Although selenium, as an important non-metallic element, has shown great application potential in optoelectronic materials, catalysts, biomedicine and other fields, there are relatively few studies on the formation mechanism of selenium-containing single crystals. At present, there are very limited reports on the artificial synthesis of selenium-containing single crystals and their crystal structure data in academia and industry. This gap in research limits our understanding of the deep-level properties of selenium-based materials and also hinders the widespread application of these materials in high-tech fields.

[0012] Selenium-containing single crystals play an irreplaceable role in photoelectric conversion, sensing technology, energy storage, etc. due to their unique physical and chemical properties. However, due to the special properties of selenium itself, such as high reactivity and volatility, the preparation process of selenium-containing single crystals is full of challenges. In addition, the diversity of selenium-based compounds also increases the complexity of crystal growth, resulting in slow progress in related research. In this context, it is particularly important to explore effective methods for the artificial synthesis of selenium-containing single crystals.

[0013] By systematically studying the formation mechanism of selenium-containing single crystals, we can not only fill the gaps in existing research, but also provide a solid theoretical basis for subsequent material design and application. At the same time, a comprehensive and detailed characterization of the crystal structure of selenium-containing single crystals can reveal the rules of its internal atomic arrangement, thereby guiding the design of new functional materials.

[0014] Exploring and mastering the method of artificially synthesizing selenium-containing single crystals is not only the key to further deepening the understanding of the crystal structure characteristics of this type of material, but also the basis for understanding its formation mechanism. This will not only help promote the development of related science and technology, but also promote the practical application of selenium-containing single crystals in more high-tech fields, and contribute to future scientific and technological progress and social development. Therefore, strengthening research in this field has important scientific value and practical significance.

[0015] Nb 3 VsS 6 Single crystals are very stable in air and are usually antiferromagnetic, but can also exhibit ferromagnetism under certain conditions. When made into nanosheets, it retains these favorable properties and, due to its nanoscale size, can also exhibit some quantum confinement effects that may enhance its magnetic behavior. Therefore, Nb 3 VsS 6 Single crystal nanosheets have a wide range of application potentials in the preparation of high-performance, low-cost magnetic devices, and have shown broad application prospects in the fields of microelectronics, spin electronics, and sensors. 3 VsS 6 The emergence of more new technologies and new applications of antiferromagnetic materials has important implications for the realization of quantum computing in the future.

[0016] A Nb 3 VsS 6 The synthesis of low-dimensional magnetic materials and their electrical resistance properties at low temperatures comprises the following steps: Step 1: Evenly mix the Nb, V, and Se raw material powders with a purity greater than 99.9% in a test tube according to the following three elements: Nb: 0.2787g, V: 0.0509g, and Se: 0.1924g; Step 2: A small amount of tellurium tetrachloride is used as a transport agent and vacuum-packed in a quartz tube with a diameter of 10 mm and a length of 200 mm; Step 3: Place the packaged sample in a dual-temperature zone tube furnace, set the temperature to rise to 950°C at a rate of 3.0°C / min, keep warm for 24 hours, then rise to 1050°C at a rate of 0.55°C / min, keep warm for 168 hours. After the high-temperature vacuum reaction is completed, take out the obtained sample to obtain high-quality magnetic Nb 3 VsS 6 Single crystal.

[0017] The present invention has the following beneficial effects: 3 VsS 6 Single crystal is a low-dimensional material with unique physical properties. It belongs to the family of transition metal trichalcogenides (TMTCs). It fills the gap in existing research and provides a solid theoretical basis for subsequent material design and application. At the same time, due to its unique crystal structure and electronic properties, this material has shown potential application value in many fields, especially in high-frequency devices, spin electronics components and magnetic dampers. 3 VsS 6 Single crystals are relatively stable in air, which is a great advantage for practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0019] Figure 1 :New material Nb 3 VsS 6 XRD measured by instrument.

[0020] Figure 2 :New material Nb 3 VsS 6 Element analysis diagram.

[0021] Figure 3 :New material Nb 3 VsS 6 Selected area electron diffraction pattern.

[0022] Figure 4 :New material Nb 3 VsS 6 High-resolution lattice image.

[0023] Figure 5 :New material Nb 3 VsS 6 Magnetic field strength test chart.

[0024] Figure 6:New material Nb 3 VsS 6 Resistance-temperature (RT) curve. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0026] A nanocrystalline magnetic material, the material is magnetic Nb 3 VsS 6 The crystal contains three elements, namely Nb, V and Se, and the molar ratio of the three elements is 3:1:6. Specifically, the atomic percentage of Nb is 30.83404%, the atomic percentage of V is 9.84943%, and the atomic percentage of Se is 59.31653%. The crystal has a hexagonal layered structure with broken centrosymmetry, and its space group is P6 3 22, V atoms are inserted between two 2H-NbS 2 Between hexagonal layers, the lattice constants are a=b=5.738Å and c=12.018Å. The magnetism in the crystal is mainly contributed by the positive trivalent Cr ions, with a magnetic moment of 3µB and a localized electron spin of S=3 / 2, while the conduction electrons originate from the unfilled bands of Nb atoms.

[0027] A method for preparing a nanocrystalline magnetic material comprises the following steps: Step 1: Mix the Nb, V, and Se raw materials with a purity greater than 99.9% according to the following three elements: Nb: 0.2787g, V: 0.0509g, Se: 0.1924g; Step 2: vacuum-packing a small amount of tellurium tetrachloride as a transport agent in a quartz tube with a diameter of 10 mm and a length of 200 mm; Step 3: Place the packaged sample in a dual-temperature zone tube furnace, set the temperature to rise to 950°C at a rate of 3.0°C / min, keep warm for 24 hours, then rise to 1050°C at a rate of 0.55°C / min, keep warm for 168 hours. After the high-temperature vacuum reaction is completed, take out the obtained sample to obtain high-quality magnetic Nb 3 VsS 6 Single crystal.

[0028] Figure 2 Nb 3 VsS 6The EDS spectrum of the single crystal sample and the surface morphology of the sample were obtained by SEM. From the EDS spectrum, we can know that the chemical composition ratio of the prepared sample is Nb: V: S = 30.83: 9.85: 59.32, which is very close to the proper ratio of the compound. The regular morphology and correct element composition ratio prove that the preparation method we adopted is very reliable.

[0029] This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can better understand and utilize the present invention.

Claims

1. A nanocrystalline magnetic material, characterized in that: The material is a magnetic Nb3VSe6 crystal, which contains three elements, namely Nb, V and Se, and the stoichiometric molar ratio of the three elements is 3:1:

6. Specifically, the atomic percentage of Nb is 30.83404%, the atomic percentage of V is 9.84943%, and the atomic percentage of Se is 59.31653%.

2. A nanocrystalline magnetic material according to claim 1, characterized in that: The crystal has a hexagonal layered structure with broken centrosymmetry. Its space group is P6322. V atoms are inserted between two 2H-NbS2 hexagonal layers. The lattice constants are a=b=5.738Å and c=12.018Å.

3. A nanocrystalline magnetic material according to claim 1, characterized in that: The magnetism in the crystal is mainly contributed by the positive trivalent Cr ions with a magnetic moment of 3µB and a local electron spin S=3 / 2, while the conduction electrons originate from the unfilled bands of Nb atoms.

4. The method for preparing a nanocrystalline magnetic material according to claim 1, characterized in that: Step 1: Mix the Nb, V, and Se raw materials with a purity greater than 99.9% according to the following three elements: Nb: 0.2787g, V: 0.0509g, Se: 0.1924g; Step 2: vacuum-packing a small amount of tellurium tetrachloride as a transport agent in a quartz tube with a diameter of 10 mm and a length of 200 mm; Step 3: Place the packaged sample in a dual-temperature zone tubular furnace, set the temperature to rise to 950°C at a rate of 3.0°C / min, keep warm for 24 hours, then increase the temperature to 1050°C at a rate of 0.55°C / min, keep warm for 168 hours. After the high-temperature vacuum reaction is completed, take out the obtained sample to obtain high-quality magnetic Nb3VSe6 single crystal.

Citation Information

Patent Citations

  • High-performance radial-assembled microsphere material of transition metal disulphide nanosheets and preparation method of high-performance radial-assembled microsphere material

    CN105226277A

  • Raman spectrum detection method for vanadium-doped transition metal chalcogenide based on characteristic peak caused by vanadium doping

    CN115656135A

  • Method for obtaining stacking superlattice based on transition metal element or chalcogenide element doping and application

    CN118835309A

  • NANO composite and manufacturing method for dispersion including the NANO composite

    KR102135221B1

  • Magnetic memory device

    US20190287637A1

Cited By

  • Nanocrystal antiferromagnetic material, preparation method and application

    CN120830156A

  • Quaternary niobium-iron-cobalt sulfide crystal, preparation method and application

    CN120866947A